A taphonomic signature for quolls in the Australian archaeological record. (June 2016) - Miscamble, Tony; Manne, Tiina
Abstract: Australian archaeofaunal assemblages are often heavily fragmented by taphonomic agents whose identity or origins are frequently difficult to discern. This study explores whether the fragmentation and accumulation of bone by carnivorous marsupial quolls may be distinguished from that produced by humans. Analyses of 140 scats obtained from captive feeding trials and wild populations of three quoll species ( Dasyurus maculatus, Dasyurus viverrinus and Dasyurus hallucatus ) indicates that damage to bones by quolls may be identified through a combination of the median length of bone specimens and observations of specific types of damage to the bone surface. Our results demonstrate that bone consumed by D. viverrinus and D. hallucatus is highly unlikely to be confused with human-accumulated assemblages due to low dietary overlap and the very small bone fragment size produced by both quoll species. Bone accumulations of the larger D. maculatus species, however, may be incorrectly attributed to humans due to the consumption of medium-large mammals by both humans and quolls, and the larger size of bone fragments produced by D. maculatus . Although fragments as large as 25 mm were recovered from wild D. maculatus scats, the median length of scat-bone fragments for D. maculatus falls between ~ 8.30–10.40 mm. This is significantly different statistically to the median fragment length (11.90 mm) of bone in scats of the Tasmanian devil, Sarcophilus harrisii, as reported by Caroline Northwood (1990). Scats from wild D. maculatus indicate that polish and pitting are the most common forms of surface damage to bone, with more than 25% of specimens displaying these marks. Punctures and tooth drag marks are far rarer, with only 5% of bone specimens exhibiting this kind of damage. In light of these results, we advocate for detailed observation of the surface of bone specimens, along with obtaining specimen lengths, in order to distinguish quoll accumulated bone in archaeofaunal assemblages. Highlights: Bone accumulated by marsupial carnivore quolls has distinguishing taphonomic features. Scat-bone accumulated by quolls can be taphonomically distinguished from archaeological accumulations. A taphonomic signature for D. maculatus may be observed through markings and measurement of scat-bone in bone accumulations. Transport or proximity of quoll latrine sites are contextual considerations for assemblages in cave and rock shelter sites.